BUSINESS PERSPECTIVE ON EXPLORING THE INTRIGUING VISTAS OF ARTIFICIAL INTELLIGENCE: Exploring the Intriguing Vistas of AI - Jovanovic, Sonja; Dražeta, Lazar; Dražeta, Bogdan; Petrović, Aleksandar (The European Journal of Applied Economics, 2025)
The capabilities of Artificial Intelligence (AI) technologies are on the rise and with the gained momentum the things that have become possible leave their users in an enigma. The boundless potential of AI reshapes reality, from 3D-printed boats and machines creating art to unveiling the uncertainty of decoding ancient conundrums and curing diseases. With the rapid advancement of this field, regulations regarding safe use of such technologies remains uncertain. This paper aims to shed light on the mysteries of AI-based predictions, while inspiring curiosity about its transformative force across industries. As humans and machines entwine, the uncertain future calls for responsible harnessing of AI power for the greater good. This mysterious odyssey that ventures into the depths of AI’s enigma is a testament to curiosity of human species, guidance, imagination’s drive, and the relentless pursuit of knowledge.